Secondary Aorto-Colonic Fistula: A Case Report and Literature Review of a Rare Complication after EVAR - Nattawadee Wiangphoem (Case Reports in Surgery)
Background: Aorto-enteric fistula (AEF) is a rare but fatal condition. The incidence of the overall AEF was approximately 0.36–2%, but the incidence of the aorto-colonic fistula was scarcely reported. A history of abdominal pain, fever, or gastrointestinal bleeding (GIB) in a patient with a history of aortic intervention should be highly suspected of this condition. This report describes a patient with lower GIB after an endovascular aneurysm repair (EVAR) for a symptomatic abdominal aortic aneurysm (AAA). Case Presentation: A 65-year-old man with a history of EVAR for symptomatic AAA presented with a massive lower GIB for two weeks. He also had a history of left lower quadrant pain and low-grade fever. Diverticular disease was suspected, and medical treatment was administered. After the initial conservative treatment, a colonoscopy was performed. The findings showed a fistula that exposed an aortic stent graft at the left-sided colon. An aorto-colonic fistula was diagnosed. After administering intravenous (IV) antibiotics, a staged axillo-bifemoral bypass graft with aortic stent graft explantation was performed. The patient recovered well and was discharged home after a month of hospitalization and IV antibiotics. Conclusion: In a patient with a history of aortic intervention, any abdominal pain, unknown fever, or even GIB should be suspected of complications of aortic intervention. Highly suspicious of this rare condition is the key to an early diagnosis and prompt treatment.